(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This roundtable explored the emerging Recognition Practices Occupational Framework as a practical guide for embedding recognition in workplaces, associations, and local ecosystems. Presented as a flexible reflection tool rather than a rigid standard, the framework maps recognition across micro, meso, and macro levels and across informal, semi-formal, and formal modalities. Its core proposition is that recognition should not be reduced to isolated credentials or “collections of pins,” but should instead support coherent pathways of recognition that make visible how people develop skills across work, volunteering, and mobility contexts. The discussion highlighted strong interest in building a more systematic “recognition function” inside organizations and across territories. Audrey Perocheau emphasized that contemporary careers are increasingly non-linear and require faster, more diversified forms of traceability than traditional diplomas alone can provide. From this perspective, digital badges, skills passports, and other forms of documented evidence can enrich understanding of individuals’ capabilities and support labor-market matching, internal mobility, and career transitions. Recognition was framed not only as a technical instrument, but also as a managerial, territorial, and political issue requiring experimentation, collective intelligence, and stronger dialogue between employers, Human Resources, public employment services, and workers. Two applied perspectives grounded the discussion. From the association sector, Vincent Godbout argued that volunteering and civic engagement are major but undervalued sites of informal learning, where people develop governance, interpersonal, and socio-cognitive skills that often remain invisible. He cautioned against over-formalizing volunteer engagement through rigid national labels, advocating instead for locally rooted recognition linked to real ecosystems of associations, municipalities, and employers. From the corporate side, Benjamin Castaldo described how the Partouche Group uses a real-time peer and manager recognition system to reward quality of work, reduce turnover, and generate open badges based on demonstrated on-the-job capability rather than formal training completion. In this model, badges make performance visible quickly, help structure progression, and can complement rather than replace training. Across the roundtable, participants stressed that recognition must remain meaningful, contextual, and trusted. Tensions emerged around standardization, social dialogue, subjectivity, and the role of trade unions, but there was broad agreement that recognizing skills acquired in work and community settings could improve retention, mobility, employability, and engagement. The session ultimately positioned the recognition function as a promising bridge between formal institutions and lived practice, with the potential by 2030 to make individuals’ full range of experiences more visible and valuable across organizations and territories. Keywords: Recognition Practices Occupational Framework, workplace and volunteer recognition, digital badges and skills passports, informal and semi-formal learning, recognition ecosystems and mobility This abstract was AI-generated from the original recording of the session and then revised by the editors for accuracy and clarity.